Effect of Madden Julian Oscillation (MJO) on Rainfall Anomalies in Bali Province 1991-2020 - Murni, Oktaviana Nurhayati; Sukarasa, I Ketut; Prasetia, Rakhmat; Wiratmaja, I Made Dwi; Abdi Bintari, Heppy Febrian (BULETIN FISIKA; Vol 24 No 2 (2023): BULETIN FISIKA August Edition, 2022)
Research has been conducted on the influence of the Madden Julian Oscillation (MJO) phenomenon of rainfall anomalies in Bali Province since 1991-2020. Research aims to figure out the conditions, anomalies, and frequency distributions rainfall in Bali Province during the existence of MJO’s 4 and 5 phase for 1991-2020 a descriptive statistical methods. The data used is daily rainfall data for 1991-2020. The results of observations from the Jembrana Class II Climatology Station and MJO data for phases 4 and 5 which monitor the presence of the MJO. The result of this study is a graph of the average rainfall calculated to inform rainfall conditions during MJO and compared to normal. Based on the results of calculations and data analysis shows Pos Candi Kuning is the post that has the most impact, this is because it has the highest increase in the amount of rainfall than normal with the highest increase of 72 mm/month occurring in March. Then for rainfall anomalies in the form of a positive anomalous percentage graph that causes increased precipitation in Bali Province. The anomaly of positive rainfall is 65% at Pos Candi Kuning. Based on the trend of the distribution of the frequency of rain events on the graph of the distribution of rainfall in the Province of Bali, generally there is an increase, but the period 2001-2005 and 2011-2015 has decreased.